Lightning: A High-Efficient Neighbor Discovery Protocol for Low Duty Cycle WSNs - Wei, Liangxiong; Zhou, Beisi; Ma, Xichu; Chen, Dexin; Zhang, Jingyu; Peng, Jian; Luo, Qian; Sun, Limin; Li, Dingcheng; Chen, Liangyin (IEEE communications letters, 2016)
In wireless sensor networks (WSNs), due to the limited energy of nodes, discovering neighbors needs to be achieved in an energy-efficient way. This means that, at a given energy consumption, we need to reduce the worst-case neighbor discovery latency as far as possible. In this letter, we propose a novel deterministic neighbor discovery method, called Lightning. Lightning employs two kinds of active slots of different active lengths (we call A slot and C slot, respectively). The active time of C slot is much shorter than that of A slot in order to reduce the energy consumption. In addition, to maximize the energy efficiency, Lightning adopts one-way neighbor discovery method. This makes C slot have the smallest active length that is only enough to send one beaconing packet. Through proactively sending one beaconing packet after one-way discovery, Lightning also realizes bi-directional neighbor discovery. The theoretical analysis indicates that, with the same energy consumption, our method reduces the worst-case latency bound up to 37.9% compared with Searchlight-Trim, the best existing discovery algorithm. The simulation verifies the soundness and effectiveness of our design.